Logistic Regression Analysis to Determine Factors Influencing Career Choices of Undergraduate Alumni: Analisis Regresi Logistik untuk Menentukan Faktor-Faktor yang Mempengaruhi Pilihan Karir Lulusan Sarjana Perguruan Tinggi - Febrian, Didi; Harliana, Putri; Farhana, Nurul Ain (KUBIK, 2025)
An undergraduate alumni has three career choices, namely work, postgraduate study or entrepreneurship. The success of an alumni's career is not only influenced by academic knowledge, but also by other factors that reflect the individual's personal and professional abilities. These factors are certainly obtained from the experiences that the alumni have gone through while studying for their undergraduate program. The respondents of this study were 100 undergraduate alumni of Universitas Negeri Medan in 2021 and 2022. This study aims to determine the effect of GPA (X1), study period (X2), number of achievements (X3), organizational activity (X4), work intensity during undergraduate (X5), and TOEFL score (X6) on alumni career choices (Y). In logistic regression analysis, the independent variable must have at least two categories so that the alumni's career choices (Y) are working (0) and postgraduate study (1). The results of the study showed that only the work intensity factor during S1 (X5) and TOEFL score (X6) had a significant influence on alumni career choices. The Logistic Regression Model based on the influential variables was . The percentage of model accuracy can predict correctly by 72.0%.